Identity, Locality and Image of the Residential House by Eko Prawoto - Elsa Intan Pratiwi; Antariksa Sudikno; Susilo Kusdiwanggo (Architectural Research Journal, 2022)
The development of residential architecture now depends on market tastes, with the trend of minimalist houses being identical in style and without a theme, as if they have lost their identity. In this case, there were many discussions that featured Eko Prawoto as an architect with the theme of local architecture, but the subject of this research questioned him. Therefore, this study discusses how the identity and concept of the natural locality of Eko Prawoto's residential works are expressed through architectural tectonics. The architectural biographical approach is used in qualitative inductive research through an emic view. The focus of this research topic is on the process of expressing the image of residential buildings through architectural tectonics. The results obtained are in the form of processing materials, techniques, and flavors in the process of building a house. This discussion is important to straighten the concept of local architecture and the meaning of architectural works through a biographical approach. This research is expected to be the basis for the use of tectonics as a basis for meaningful architectural development.